Penggunaan WhatsApp Business sebagai Media Komunikasi Pemasaran Digital UD. Wijaya Cipta Abadi - Ikaningtyas, Maharani; Izzuddin, Aufa; Pramesti, Vania Amanda; Azizah, Farikhah Nur (Jurnal Bisnis Indonesia, 2024)
Technological developments in this digital era present various social media applications, one ofwhich is WhatsApp. Early in its development, social media was used as a medium of communicationbetween individuals and groups. However, currently, social media can be used by businesses as amedium of marketing communication with their consumers. WhatsApp Business is a social mediaapplication that can be used as a marketing communication medium for a business, includingMSMEs. In Karangsari Village there are various MSMEs with conventional product marketingproblems and marketing coverage is only limited to the nearest area. UD. Wijaya Cipta Abadi is oneof the MSMEs in Karangsari Village that is experiencing this problem. This service aims to introduceWhatsApp Business and its feature functions to UD. Wijaya Cipta Abadi is a digital marketingcommunication medium. The methods used in this service are Focus Group Discussion (FGD),counseling, and training. The result of this dedication is UD. Wijaya Cipta Abadi has a WhatsAppBusiness account and can operate its features to market their products. This service is only limited tointroducing the application and its feature functions, as well as creating a WhatsApp Businessaccount.Keywords: Marketing Communications; MSMEs; WhatsApp Business